The Ideological and Political Education in English Reading Classes in Junior Middle School: An Analysis with An Exemplary Case - 徐异环 (Pacific International Journal, 2022)
Abstract:Traditional contemporary education is more focused on cultivating students’ test-taking ability. There is an incorrect tendency to value grades over soft culture, which does not meet the requirements of cultivating students in the new era. This study mainly uses the questionnaire survey method and documentary analysis method to study the possibility and results of applying Ideological and Political Education in secondary school English classrooms. The following research questions were mainly answered: (1) How can teachers integrate the Ideological and Political pedagogy into English reading classroom teaching? (2) What kind of impact can ideological and political education have on students in reading classes? The study concluded the survey , clarified the necessity and research value of the thinking and government teaching method at present, and analyzed and summarized the revelations and lessons: ideological and political education should be and can be carried out from three aspects: the individual and the state, the individual and society, and the individual and the self. It should be carried out with the state and society as the solid force, the teaching goal of teaching and education as the core, the teacher as the active initiator, and the reading classroom should be carried out as an important carrier. The student’s enthusiasm for learning was significantly increased after combining the Ideological and Political Science teaching methods, and their recognition of Civic and Chinese mainstream values was increased. We should vigorously promote Ideological and Political Science education and skillfully integrate it into all aspects of teaching.